Towards an artistic decolonial didactics. A proposal in the intercultural classroom from the Misak community (2020)
The current study was developed with 25 students from 2nd and 3rd grade of La Campana school, this institution is in the town of Guambia (Cauca). The main objective was to generate a strengthening of the traditional artistic practices of the Misak indigenous population through a didactic proposal that starts from the ideals of the so-named Decolonial Pedagogies from an intercultural didactic model. In terms of the methodology, a qualitative study was carried out, from the action research perspective. The techniques developed to collect the information were analysis of the Journals that emerged from the activities, and interviews carried out in different sectors in charge of the school The results evidenced that the artistic themes considering the own and intercultural tradition conceived an approach and appreciation for the own culture, because it is necessary to generate new educational practices and Decolonial Didactic strategies, which strengthen the know-how of the Educational Institution and, at the at the same time, traditional knowledge.